Mindful Leadership Development: Investing in the Academy - Christy A. Crutsinger Ph.D.; Angela Wilson Ph.D.; Eugene Martin M.F.A.; Alan Albarran Ph.D.; Dawna Wilson Ph.D. (Academic Chairpersons Conference Proceedings, 2015)
While universities need leaders capable of initiating and sustaining change, few institutions provide the requisite training and development that equips academic administrators to be effective leaders. This session will highlight a comprehensive, institutional approach for leadership development that addresses the needs of current and future faculty leaders across the pipeline. http://facultysuccess.unt.edu
Keywords: leadership; development; chair; leaders; programs